2019
DOI: 10.3390/microorganisms7120688
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Bovine Mammary Epithelial Cell Line by Ruminant-Associated Staphylococcus aureus is Lineage Dependent

Abstract: Bovine mastitis is a costly disease to the dairy industry and intramammary infections (IMI) with Staphylococcus aureus are a major cause of mastitis. Staphylococcus aureus strains responsible for mastitis in cattle predominantly belong to ruminant-associated clonal complexes (CCs). Recognition of pathogens by bovine mammary epithelial cells (bMEC) plays a key role in activation of immune responsiveness during IMI. However, it is still largely unknown to what extent the bMEC response differs according to S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…In the peracute gangrenous subgroup, 44% of the isolates belonged to CC133. Interestingly, the S. aureus isolates of CC133 induced a significantly stronger interleukin 8 (IL-8) release from bovine mammary epithelial cells in cell culture than isolates from the other CCs ( Hoekstra et al, 2019 ). In the 11 European countries that participated in the study by Hoekstra et al (2020) , the proportion of CC133 in each country varied from 0 to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…In the peracute gangrenous subgroup, 44% of the isolates belonged to CC133. Interestingly, the S. aureus isolates of CC133 induced a significantly stronger interleukin 8 (IL-8) release from bovine mammary epithelial cells in cell culture than isolates from the other CCs ( Hoekstra et al, 2019 ). In the 11 European countries that participated in the study by Hoekstra et al (2020) , the proportion of CC133 in each country varied from 0 to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…First, the low common DEGs and DSGs induced by different S. aureus lineages showed the great heterogeneity of host immune responses to different S. aureus lineages. The challenge of S. aureus strains with different lineages in bovine mammary epithelial cells results in the differential expression of genes related to inflammation [ 9 , 32 ]. Among which, only a few candidate genes were tested by low-throughput qPCR or ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…In the mastitis cell model, a previous study observed that the transcriptional expression levels of several candidate genes in primary bovine mammary epithelial cells (pbMECs) or Mac-T cells line are significantly different for different S. aureus lineages challenge [ 8 ]. For the host, the mammary epithelial cells in mammary gland establishes the first physical line of defense against the external pathogen, and a healthy mammary gland is vital in mobilizing the early innate immune response [ 9 , 10 ]. In our previous study, we isolated and cultured 191 S. aureus strains, including five MRSA strains, from bovine milk across nine Holstein dairy farms [ 11 , 12 ], and found that S. aureus is widely distributed in cows with different inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…These pathogenic bacteria include both Gram-positive bacteria, e.g., Staphylococcus aureus (S. aureus), Streptococcus agalactiae, Streptococcus spp., etc., as well as Gram-negative bacteria, such as Escherichia coli (E. coli), Klebsiella spp., Enterobacter spp., etc. [6][7][8][9][10]. E. coli and S. aureus are amongst the most common and important pathogens to induce mastitis [1,11].…”
Section: Introductionmentioning
confidence: 99%